2011
DOI: 10.20452/pamw.1077
|View full text |Cite
|
Sign up to set email alerts
|

Do circulating antibodies against C1q reflect the activity of lupus nephritis?

Abstract: IntroductIonThe results of recent studies suggest that there is a link between the presence of antibodies against C1q (anti-C1q Abs) and kidney involvement in systemic lupus erythematosus (SLE). However, it remains unclear whether the clinical symptoms of lupus nephritis (LN) may be associated with the presence of anti-C1q Abs in serum.objEctIvEs The aim of the study was to compare the prevalence and levels of anti-C1q Abs and antibodies against double-stranded DNA (anti-dsDNA Abs), circulating immune complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[2][3][4] In Polish conditions, circulating anti-C1q antibodies have been recently studied as the marker for lupus nephritis, while anti-ribosomal P protein antibodies titer and IL-10 concentration in exhaled breath condensate as general markers of the disease activity. [5][6][7] The search for new SLE activity markers is ongoing. In recent years, the effectiveness of marking the β2-microglobulin (β2M) serum concentrations in monitoring SLE activity has been consistently highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In Polish conditions, circulating anti-C1q antibodies have been recently studied as the marker for lupus nephritis, while anti-ribosomal P protein antibodies titer and IL-10 concentration in exhaled breath condensate as general markers of the disease activity. [5][6][7] The search for new SLE activity markers is ongoing. In recent years, the effectiveness of marking the β2-microglobulin (β2M) serum concentrations in monitoring SLE activity has been consistently highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…After full text identification, 93 citations were excluded for the following reasons: mechanism studies, quantitative data without cut-off value, statistical analysis without relative risk or odds ratio (OR), SLE patients without renal involvement were not included as a control group or two by two fourfold table cannot be constructed. Ultimately, only 25 studies8,[10][11][12]16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] met the eligibility criteria of the meta-analysis, among them 22 studies8,10,12,16,[25][26][27][28][29][31][32][33][34][35][36][37][38][40][41][42][43] had sufficient data for the analysis in LN diagnosis and 9 studies10,…”
mentioning
confidence: 99%
“…In patients with detected anti-C1q antibodies, the presence of microhaematuria (59% vs 16%, P = 0.003), urinary casts (28% vs 8%, P = 0.02), and low levels of serum C3 ( P = 0.03) and C4 ( P = 0.01) is significantly higher. 4 Stojan and Petri 5 have shown that anti-C1q in combination with anti-dsDNA and low complement have the strongest serological association with renal involvement. Furthermore, data show that anti-C1q antibodies correlate with a histopathological type of nephritis.…”
Section: Anti-c1q Autoantibodiesmentioning
confidence: 99%